Znaczenie świadectwa wiary rodziców w wychowaniu religijnym ich dzieci - Skreczko, Adam (Studia Pastoralne, 2026)
The faith of parents is an important factor to be taken into account while weighing the problem of educating children. The parent’s part in religious upbringing of their children is constant meeting the challenges which are the consequence of the sacrament of baptism and the tasks it imposes. The problem is vital, because in the process of religious upbringing the parents should be witnesses, not only instructors. The child’s faith is built on the faith of his parents, who, in their lives, should be authentic witnesses of their faith. They should create appropriate situations that may stimulate their children’s willingness to meet God. Simultaneously, they should observe their children’s spiritual development, without using any forms of pressure. The parent’s faith is an example for a young growing person how to get to know God. Christian parents should not only talk about Christ, but also let their children know Him through their own testimony of life and love.